2004
DOI: 10.1002/erv.604
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction for longevity: II—The systematic neglect of behavioural and psychological outcomes in animal research

Abstract: Research on caloric restriction for longevity (CRL) has generated hundreds of articles on the physiology of food deprivation, yet almost no data on consequences in other domains. The first paper in this series outlined the generally positive physical effects of CRL; the second analyses the meagre and sometimes disturbing record of research on behaviour, cognition and affect. The available evidence suggests that nutrient-dense CRL in animals-just like nutrientpoor semi-starvation in people-is associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 102 publications
1
24
0
1
Order By: Relevance
“…3 The results of the present study add to the literature by addressing some of the limitations of previous studies. First, a group of nondieting middle-age men and women were recruited for this randomized controlled trial.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…3 The results of the present study add to the literature by addressing some of the limitations of previous studies. First, a group of nondieting middle-age men and women were recruited for this randomized controlled trial.…”
Section: Discussionsupporting
confidence: 56%
“…2 As calorie restriction research moves from animal models to human trials, it is important to measure the full effect of calorie restriction on cognition, including learning and memory. 3 Calorie restriction inhibits age-related cognitive decline in rats, 4 yet a number of human studies report that self-reported dieting or calorie restriction is associated with cognitive impairment, e.g., memory, attention, processing speed, and concentration deficits. 5-9 However, cognitive impairment is frequently mediated by self-reported dieters' preoccupying thoughts about food and body weight/shape.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CR or the intent to restrict intake has been associated with the onset of eating disorders, including anorexia (105) and bulimia nervosa (65), and binge eating disorder (106). Hence, there is a need to examine both the benefit and potential harm of CR in humans, particularly for people who are not obese, and to answer important safety questions before CR is recommended (93,94).…”
Section: Development Of Eating Disorder Symptomsmentioning
confidence: 99%
“…Additionally, CR or the intent to restrict intake has been associated with the onset of eating disorders, including anorexia [48] and bulimia nervosa [49], and binge eating disorder [50]. Hence, there is a need to examine both the benefit and potential harm of CR in humans, particularly for people who are not obese, and to answer important safety questions before CR is recommended [51,52].…”
Section: A Development Of Eating Disorder Symptomsmentioning
confidence: 99%